2018
DOI: 10.1016/j.cogdev.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The development of counterfactual reasoning about doubly-determined events

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 41 publications
5
51
2
Order By: Relevance
“…Some interesting studies have shown that children around five years old were able to interpret counterfactual conditionals in the discriminate condition. This was shown by McCormack, Ho, Gribben, O'Connor, and Hoerl [22] and by Nyhout and Ganea [23] (see also [24]). They used two very simple tasks with few objects and the conditionals were about physical causation: the effects on the objects of simple actions.…”
Section: Plos Onementioning
confidence: 63%
See 1 more Smart Citation
“…Some interesting studies have shown that children around five years old were able to interpret counterfactual conditionals in the discriminate condition. This was shown by McCormack, Ho, Gribben, O'Connor, and Hoerl [22] and by Nyhout and Ganea [23] (see also [24]). They used two very simple tasks with few objects and the conditionals were about physical causation: the effects on the objects of simple actions.…”
Section: Plos Onementioning
confidence: 63%
“…They used two very simple tasks with few objects and the conditionals were about physical causation: the effects on the objects of simple actions. The question was formulated using "counterfactual expressions" in [22] but including the "if. .…”
Section: Plos Onementioning
confidence: 99%
“…However, evidence suggests that children can reason counterfactually about overdetermined physical events—compared to events involving human agents in narratives—by the age of 4 (Nyhout & Ganea, ) or 6 years (McCormack, Ho, Gribben, O’Connor, & Hoerl, ). For example, preschoolers in one study were familiarized with a box that lit up when certain types of blocks were placed on it (Nyhout & Ganea, ).…”
Section: A Framework For the Development Of Counterfactual Reasoningmentioning
confidence: 99%
“…For instance, adults judge physical events as more deterministic than psychological ones (Strickland, Silver, & Keil, ). Comparing across studies, the findings suggest that children are more successful at reasoning counterfactually about physical systems (McCormack et al, ; Nyhout & Ganea, ) than about structurally similar problems involving human agents (Nyhout, Henke, et al, ; Rafetseder et al, ) and biological causal systems (Nyhout, Sweatman, et al, ). This could be because children perceive physical events as more deterministic.…”
Section: A Framework For the Development Of Counterfactual Reasoningmentioning
confidence: 99%
“…Two recent studies have used doubly determined events, where a single outcome has more than one potential cause, to try to ensure that children had to consider the specific events in the past. In McCormack et al (2018), two birds travelled down two separate slides towards a pig. If they reached this pig, it would get knocked over, but sometimes their paths were blocked.…”
mentioning
confidence: 99%